Konjac supplementation can alleviate obesity induced by high-fat diet in mice by modulating gut microbiota and its metabolites - Yuhang Wen; Baoting Chen; Jingrong Huang; Yadan Luo; Shuya Lv; Hao Qiu; Shuaibing Li; Songwei Liu; Lvqin He; Manli He; Zehui Yu; Mingde Zhao; et al. (Current Research in Food Science)
As a multi-factorial disease, obesity has become one of the major health problems in the world, and it is still increasing rapidly. Konjac supplementation, as a convenient dietary therapy, has been shown to be able to regulate gut microbiota and improve obesity. However, the specific mechanism by which konjac improves obesity through gut microbiota remains to be studied. In this study, a high-fat diet (HFD) was used to induce a mouse obesity model, and 16S rDNA sequencing and an untargeted metabolomics were used to investigate the impact of konjac on gut microbiota and gut metabolites in HFD-induced obese mice. The results show that konjac can reduce the body weight, adipose tissue weight, and lipid level of high-fat diet induced obese mice by changing the gut microbiota structure and gut metabolic profile. Association analysis revealed that konjac supplementation induced changes in gut microbiota, resulting in the up-regulation of 7-dehydrocholesterol and trehalose 6-phosphate, as well as the down-regulation of glycocholic acid and ursocholic acid within the Secondary bile acid biosynthesis pathway, ultimately leading to improvements in obesity. Among them, g_Acinetobacter (Greengene ID: 911888) can promote the synthesis of 7-dehydrocholesterol by synthesizing ERG3. g_Allobaculum (Greengene ID: 271516) and g_Allobaculum (Greengene ID: 259370) can promote the breakdown of trehalose 6-phosphate by synthesizing glvA. Additionally, the down-regulation of glycocholic acid and ursocholic acid may be influenced by the up-regulation of Lachnospiraceae_NK4A136_group. In conclusion, konjac exerts an influence on gut metabolites through the regulation of gut microbiota, thereby playing a pivotal role in alleviating obesity induced by a high-fat diet.